Lyre and trellis training systems on the berry composition of 'Cabernet Sauvignon' in the Brazilian highlands - Marcon Filho J.L.* (2017)
Training systems involve a manipulation of vine form, directly influencing the composition of the fruit. Through interaction with the environment, training systems may represent an influence in winemaking, too. The present study aims to investigate the effect of the training systems on productivity, physical and chemical characteristics of 'Cabernet Sauvignon' grape berries, in order to establish criteria that will determine the most appropriate management for red winemaking in regions above 900 m in altitude. The experiment was conducted during the 2011 and 2012 vintages, in vineyards of 'Cabernet Sauvignon' grafted on 'Paulsen 1103', implemented in 2004, at a spacing of 3.0×1.5 m. Treatments consisted of two training systems (lyre and trellis) in three vineyards at Painel, Urubici and São Joaquim counties, Santa Catarina State, Brazil, 1,200, 1,150 and 1,340 m in altitude, respectively. The results showed that productivity, berry weight and the relation skin/berry, were higher in the lyre system. Soluble solids, acidity, anthocyanins, hue and intensity colour berry did not differ between both systems. The lyre training system is recommended for 'Cabernet Sauvignon' in the highlands of Santa Catarina State, Brazil, seeing that it had superior productivity, and chemical composition was similar or better than the trellis system.